Maternal Exercise Improves High-Fat Diet-Induced Metabolic Abnormalities and Gut Microbiota Profiles in Mouse Dams and Offspring - Zhou, Liyuan; Xiao, Xinhua; Li, Ming; Zhang, Qian; Yu, Miao; Zheng, Jia; Deng, Mingqun (Frontiers in Cellular and Infection Microbiology, 2020)
Early-life overnutrition programs increased risks of metabolic disorders in adulthood. Regular exercise has been widely accepted to be an effective measure to maintain metabolic health. However, the intergenerational effects of maternal exercise and the specific mechanism are largely unclear. Our objective was to investigate whether maternal exercise could alleviate the metabolic disturbances induced by early-life overnutrition in both dams and offspring and to explore the role of gut microbiota in mediating the effects. C57BL/6 female mice were randomly divided into three groups: the control group, which were fed a normal control diet; high-fat group, which received a high-fat diet; and high-fat with exercise intervention group, which was fed a high-fat diet and received a voluntary wheel running training. The diet intervention started from 3 weeks prior to mating and lasted throughout pregnancy and lactation. The exercise intervention was only prior to and during pregnancy. The male offspring got free access to normal chow diet from weaning to 24 weeks of age. Glucose tolerance test and biochemical parameters were detected in dams at weaning and offspring at 8 and 24 weeks of age. Their cecal contents were collected for the 16s rDNA amplicon sequencing. The results showed that maternal high-fat diet resulted in significant glucose intolerance, insulin resistance, and lipid profiles disorders in both dams and offspring. Maternal exercise markedly improved insulin sensitivity in dams and metabolic disorders in offspring from young into adulthood. The decrease in unfavorable bacteria and the persistent enrichment of short-chain fatty acids-producers from mothers to adult offspring, particularly the genus Odoribacter, were all associated with the improvement of metabolism by maternal exercise. Overall, maternal exercise could significantly mitigate the detrimental effects of a maternal high-fat diet on metabolism in both dams and male offspring. The continuous alterations in gut microbiota might be a critical factor in deciphering the metabolic benefits of maternal exercise, which provides some novel evidence and targets for combating metabolic diseases.